ANALISIS STRES KERJA PEGAWAI PADA KANTOR PEGADAIAN CABANG CINERE KOTA JAKARTA SELATAN - Putri Lestari, Agung; Darmawan, Aulia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study, entitled "An Analysis of Employee Work Stress at the Pegadaian Branch Office in Cinere, South Jakarta," aims to determine the causes of work stress. The research method employed was descriptive qualitative research. Data collection techniques included observation, interviews, focus group discussions (FGDs), and documentation. The results of this study, obtained from interviews with the participants, indicate that factors influencing employee work stress include workload, time demands, pressure, work overload, piling up work, and both internal and external factors. Employees' solutions to cope with work stress include traveling, pursuing hobbies, engaging in activities they enjoy, seeking entertainment, resting, praying, and exercising. The study concluded that all employees at the Pegadaian Branch Office in Cinere, South Jakarta, experience work stress due to work demands and workloads that are not commensurate with their abilities. To cope, most employees choose traveling and praying